Performance of maximum-largest weighted delay first algorithm in long term evolution-advanced with carrier aggregation - Mohd. Ramli, Huda Adibah (Institute of Electrical and Electronics Engineers Inc., 2014)
Guaranteed Bit Rate (GBR) applications with strict Quality of Service (QoS) are getting increasingly popular among mobile cellular users. These delay-sensitive applications demand for a large bandwidth for transmission over the mobile cellular systems. Long Term Evolution-Advanced (LTE-A) that supports a wider transmission bandwidth is expected to meet this crucial demand. Packet scheduling is one of the key features as the LTE-A delivers these applications using packet-switching technology. To optimize packet scheduling performance for supporting the GBR applications, this paper adapts a well-known single-carrier Maximum-Largest Weighted Delay First (M-LWDF) algorithm into the multi-carrier downlink LTE-A. Simulation results have demonstrated that the adapted M-LWDF algorithm that performs packet scheduling on each radio resource, takes packet delay and the aggregated average throughput across all component carriers into consideration is more efficient for supporting the delay-sensitive GBR applications in the downlink LTE-A.